Pengaruh Pengembangan Produk, Persepsi Masyarakat, dan Keamanan terhadap Evaluasi Kinerja Bank Syariah Indonesia Kota Bandar Lampung - Indra Al Fitara; Moh Bahrudin; Anggun Okta Fitri (Yayasan Literasi Sains Indonesia, 2025)
This study highlights the importance of performance assessment of Indonesian Islamic Banks, especially Bandar Lampung Islamic Bank, which is influenced by product development, public perception, and security. The purpose of the study was to examine the impact of these three factors on bank performance assessment and determine the relative importance of each in the success of Islamic banks. The results of the analysis show that product development has a positive but insignificant impact, with a t-value (-306) smaller than the t-table (1.98217) and a significance (0.760) greater than 0.05. In contrast, public perception and security show a positive and significant impact, with t-values ​​of 5.154 and 2.909, respectively, and a significance below 0.05. These findings indicate that this study, although with important product development, security and public opinion have a greater influence on the performance of Islamic banks. Therefore, banks need to focus on improving transaction security, service quality, and transparency to build consumer trust. This study provides insight for Islamic bank management to improve performance and competitiveness in the Indonesian Islamic banking market.